Abordagens sobre o tempo na música contemporânea - Barreiro, Daniel Luis (2000)
In this research the musical time is understood as one of the perceptual results the musical work can generate on a certain listener. Musical time is, therefore, a result of the perception process which, somehow, is motivated by the characteristics contained in the musical work. Therefore, when one studies the issue from the point of view of the composition, one searches the main musical aspects contained in the musical work that motivate this temporal result on the listener. Some of the authors mentioned here try to foresee such result. Our interest is different. We try to point out different ways to think the musical time in composition, directing our curiosity to the compositional ideas that may be generated from this reflection on the subject. From the study carried out here, we present some considerations on temporal discontinuity and staticity, and we elaborate five manners in order to generate contractions and dilatations of the musical time in the composition. They are: velocity, density of events, previsibility level, impact and digression. Heading from some considerations concerning the attempt to foresee the listener s temporal perception, we present a compositional proposal. Finally, we point out some initial relations between the study of time in music and in Peirce s semiotics, which we believe to be able to generate contributions to the contemporary compositional thought in future researches